Development Of Web-Based Hybrid Learning Information Systems Esa Unggul University (Case Study: Superior Esa University) - Anwar, Nizirwan; Rahmahati Jamiandani, Syarah; Adikara, Fransiskus; Lestari, Sri (International Journal of Psychosocial Rehabilitation, 2020)
Blended Learning or also called Hybrid Learning is conceptualized as a combination of several learning models that include face-to-face integrated learning with learning activities that use computer-based learning media, where the integration of learning concepts aims to optimize learning activities better, learning system users has become a necessity in the world of education, especially in universities. Esa Unggul University is a campus that already uses online learning. The problem felt by students is not being able to feel the real situation such as communication, interaction. The solution is to make Hybrid Learning more interactive and more tangible because it can communicate, discuss with classmates and lecturers directly. In direct learning like this, students download or look at it first when they want to see a video or learning module, working on material that sometimes students don’t really understand the material taught, as well as quizzes. learning by using the PIECES method for analysis, the development of a prototyping system that is supported using webbased technology by providing various learning information options such as videos and writing that provide information about achievement and learning. This research resulted in the development of learning media with the use of web-based technology that helps improve learning that is attractive and attractive with a link connected to the YouTube site that explains learning in accordance with the courses taken and choices in learning such as attendance, quizzes, materials and forms. chat, as well as information in the form of learning or education to help lecturers monitor online lectures and help students not to be involved in classroom learning.